Direct numerical simulation of packed and monolith syngas catalytic combustors for micro electrical mechanical systems - Bazooyar, Bahamin; Zhu, Mingming; Manovic, Vasilije; Nabavi, Seyed Ali (Elsevier, 2023)
In this work, a catalytic combustor for micro electrical mechanical system for syngas was designed and analysed using Direct Numerical Simulation (DNS) in conjunction with finite rate chemistry. The effect of catalyst (platinum (Pt), palladium (Pd), palladium oxide (PdO), and rhodium (Rh)), bed type (packed with twelve catalyst shapes and four catalyst monolith), shapes (packed: cylinder, hollow cylinder, four cylinder, single cylinder, single cylinder, cross-webb, grooved, pall-ring, hexagonal, berl-saddle, cube, intalox-saddle, and sphere, monolith: triangular, rectangular, hexagonal, and circular), and operating conditions (inlet temperature and velocity, fuel/air ratio, different concentrations CH4-H2-CO) on combustion efficiency and pressure drop were studied using different parameters (combustion efficiency (η), pressure drop, effectiveness factor (Ψ), and fuel conversions (H2 and CH4 conversions)). Analysis under different operating conditions reveals that the designed combustor can operate effectively with syngas of varying compositions with a high combustion efficiency of over 85%. Combustion mainly takes place on the surface of the catalyst without gas phase reaction with pressure drops between 18 Pa and 155 Pa. The intalox saddle shape catalysts resulted in the bed effectiveness factor 0.93.1 The Damköhler for hydroxyl radicals (OH) over the entire length of the reactor is uniformly distributed and well below 3, suggesting uniform combustion.
Keywords: Hydrogen; Catalytic combustor; Combustion; DNS; Flameless; MEMS